COMMON FIXED POINT THEOREMS FOR TWO PAIRS OF SELFMAPS SATISFYING GENERALIZED WEAK CONTRACTIVE CONDITION - Babu, G.V.R.; Kidane, K.T. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we prove a common fixed point theorem for two pairs of weakly contractive selfmaps satisfying certain generalized weakly contractive type inequality. Also, we prove the same for two pairs of such selfmaps in which one pair is compatible, reciprocally continuous and the other pair is weakly compatible. Some existing results are drawn as corollaries from the main results of this paper. Examples are given in support of the main results of the paper.